1986
DOI: 10.1017/s002221510010009x
|View full text |Cite
|
Sign up to set email alerts
|

The role of radiography in the management of nasal fractures

Abstract: The role of radiographs in the management of nasal fractures is assessed. The inj ury is common and the total cost of radiographs significant. A retrospective study concluded that radiographs were not definitive in the management of nasal fractures. This prompted a prospective study, in which 54 patients were assessed clinically, radiologically and under anaesthesia. At each stage they were grouped into treatment and pathological categories and the contribution of each type of assessment studied. Radiographs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 6 publications
0
30
0
1
Order By: Relevance
“…Diagnosis was confirmed in all cases with radiographic evaluation (lateral nasal bone radiograph) for medicolegal reasons. 6 The need for radiograph is controversial and in many places it is actively discouraged, Logan et al also concluded that they are not cost-effective only utility is proof of fracture in subsequent litigation.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis was confirmed in all cases with radiographic evaluation (lateral nasal bone radiograph) for medicolegal reasons. 6 The need for radiograph is controversial and in many places it is actively discouraged, Logan et al also concluded that they are not cost-effective only utility is proof of fracture in subsequent litigation.…”
Section: Discussionmentioning
confidence: 99%
“…Clayton & Lesser (1986) studied 54 patients with nasal injuries and concluded that standard radiographs were not useful in their management.…”
Section: Discussionmentioning
confidence: 99%
“…Annals of Plastic Surgery • Volume 53, Number 6, December 2004 cient 4,6 and that CT is very useful for diagnosis and treatment. [7][8][9] This remains true postoperatively.…”
Section: Yabe Et Almentioning
confidence: 99%
“…Poor reduction causes secondary deformity after the swelling subsides. 1 The correct diagnosis of nasal fracture cannot be made by x-ray findings alone, 4,6 and the usefulness of computed tomography (CT) is well known. [7][8][9] In the same way, the postoperative condition cannot be adequately demonstrated on x-ray findings alone, and CT examination is necessary.…”
mentioning
confidence: 99%